2019
DOI: 10.21203/rs.2.9611/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional insights into the Diabrotica virgifera virgifera ATP-binding cassette transporter gene family

Abstract: Background The western corn rootworm, Diabrotica virgifera virgifera , is a pervasive pest of cultivated maize in North America and Europe, which has adapted to survive exposure to multiple insecticidal agents. Due to their role in insecticide transport, we sought to identify members of the ATP-binding cassette (ABC) transporter family in D. v. virgifera using a transcriptomics approach.Results In this study, 65 putative D. v. virgifera ABC ( Dvv ABC) transporters were identified within a combined transcript… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…ATP-binding cassette transporters comprise one of the largest gene families wherein subfamilies A-H in arthropods function in a variety of transmembrane transport activities [114], including involvement in development [115] and detoxification [116], and potentially in Bt resistance mechanisms. There are 188 complete and partial RefSeq annotated ABC transporters in Dvir_2.0, which is greater than a transcriptome-based estimate of 65 from a prior D. v. virgifera transcriptome-based estimate [117]. Phylogenetic reconstruction using 93 Dvir_2.0 models containing a full-length NDB placed 10 members into an ABCB clade, suggesting the number of orthologs are nearly double that predicted in T. castaneum and equal to that in A. viridicyanea.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…ATP-binding cassette transporters comprise one of the largest gene families wherein subfamilies A-H in arthropods function in a variety of transmembrane transport activities [114], including involvement in development [115] and detoxification [116], and potentially in Bt resistance mechanisms. There are 188 complete and partial RefSeq annotated ABC transporters in Dvir_2.0, which is greater than a transcriptome-based estimate of 65 from a prior D. v. virgifera transcriptome-based estimate [117]. Phylogenetic reconstruction using 93 Dvir_2.0 models containing a full-length NDB placed 10 members into an ABCB clade, suggesting the number of orthologs are nearly double that predicted in T. castaneum and equal to that in A. viridicyanea.…”
Section: Discussionmentioning
confidence: 89%
“…The unordered genomic contigs generated by SOAPdenovo were joined based on sequential gapped alignments with two transcript assemblies. The first round of transcript-guided scaffolding used 87,996 transcripts assembled across different growth stages (NCBI TSA accession GHNJ00000000.1 [117] to query against the D. v. virgifera SOAPdenovo GapCloser assembly with the BLASTlike alignment tool (BLAT) [163]. Searches used default parameters, except that the resulting.psl file header was suppressed (-noHead) and minimum sequence identity (-minIdentity) was set at 0.95.…”
Section: Genome Sequencing and Scaffold Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a maximum likelihood analysis using the ABC transporters identified in the present study and those from T. castaneum and D. virgifera virgifera (Adedipe et al, 2019; Broehan et al, 2013). Phylogenetic analysis indicated that they are classified into eight subfamilies (ABCA‐H) with high bootstrap values, among which ABCC and ABCG were the largest subfamilies (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple amino acid sequence alignment of the ABC transporters identified in this study and those from T. castaneum (Broehan et al, 2013) and Diabrotica virgifera virgifera identified from transcriptomic data (Adedipe et al, 2019) were performed using the MUSCLE package with default parameters in MEGA X (Kumar et al, 2018). ABC transporters used for phylogenetic analysis are listed in Supporting Information: Table .…”
Section: Methodsmentioning
confidence: 99%